Electrical and Thermal Studies on the Polyvinylchloride/Carbon Black Composites Induced by High Energy Ion Beam - GÜLLÜOĞLU, ARİF NİHAT (TAYLOR & FRANCIS LTD, 2010)
Modification induced by energetic ion in polyvinylchloride (PVC)/carbon black (CB) composites was studied using impedance gain-phase analyzer, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Different concentrations of CB were dispersed in PVC films. These films were irradiated with 140 MeV Ag11+ ions at the fluences of 1 x 10(11) and 1 x 10(12)ions/cm(2). The ac electrical conductivity and dielectric response were studied as a function of filler, frequency and ion fluence. It was found that ac electrical conductivity increases with increasing the percentage of CB, frequency and ion fluence. The observed enhancement in ac electrical conductivity is attributed to the increase in the number of conduction paths created by the carbon black contents in the composites to give a higher electrical conductivity. An increase in dielectric constant was observed with the ion fluence and also with the carbon black content, which is attributed to the interfacial polarization of heterogeneous systems. Differential scanning calorimetry (DSC) analysis showed that the glass transition temperature (Tg) shifted towards lower temperature with increasing the ion fluence. It may be attributed to the scissioning of polymer chains and as a result increase of free radicals, unsaturation etc., which lead to the transformation of polymer into amorphous phase. Atomic force microscopy (AFM) studies revealed that the surface average roughness of the composites increases as filler concentration increases and decreases upon irradiation. SEM micrographs showed that carbon black particles organized into aggregates of micro spherical voids and decreased its size upon irradiation.
Keywords: PVC/CB composites; ion beam modification; electrical properties; differential scanning calorimetry; atomic force microscopy; CARBON-BLACK; CONDUCTIVITY; FILMS